Assessment of Small Cellular Particles from Four Different Natural Sources and Liposomes by Interferometric Light Microscopy - Romolo, Anna; Jan, Zala; Bedina Zavec, Apolonija; Kisovec, Matic; Arrigler, Vesna; Spasovski, Vesna; Podobnik, Marjetka; Iglič, Aleš; Pocsfalvi, Gabriella; Kogej, Ksenija; Kralj-Iglič, Veronika (International journal of molecular sciences, 2022)
Small particles in natural sources are a subject of interest for their potential role in intercellular, inter-organism, and inter-species interactions, but their harvesting and assessment present a challenge due to their small size and transient identity. We applied a recently developed interferometric light microscopy (ILM) to assess the number density and hydrodynamic radius (Rh) of isolated small cellular particles (SCPs) from blood preparations (plasma and washed erythrocytes) (B), spruce needle homogenate (S), suspension of flagellae of microalgae Tetraselmis chuii (T), conditioned culture media of microalgae Phaeodactylum tricornutum (P), and liposomes (L). The aliquots were also assessed by flow cytometry (FCM), dynamic light scattering (DLS), ultraviolet-visible spectrometry (UV-vis), and imaging by cryogenic transmission electron microscopy (cryo-TEM). In Rh, ILM showed agreement with DLS within the measurement error in 10 out of 13 samples and was the only method used here that yielded particle density. Cryo-TEM revealed that representative SCPs from Tetraselmis chuii flagella (T) did not have a globular shape, so the interpretation by Rh of the batch methods was biased. Cryo-TEM showed the presence of thin filaments in isolates from Phaeodactylum tricornutum conditioned culture media (P), which provides an explanation for the considerably larger Rh obtained by batch methods than the sizes of particles observed by cryo-TEM images. ILM proved convenient for assessment of number density and Rh of SCPs in blood preparations (e.g., plasma); therefore, its use in population and clinical studies is indicated.